Perioperative glycemic management in adults presenting for elective cardiac and non-cardiac surgery - Roshni Sreedharan; Sandeep Khanna; Andrew Shaw (Perioperative Medicine, 2023)
Abstract Perioperative dysglycemia is associated with adverse outcomes in both cardiac and non-cardiac surgical patients. Hyperglycemia in the perioperative period is associated with an increased risk of postoperative infections, length of stay, and mortality. Hypoglycemia can induce neuronal damage, leading to significant cognitive deficits, as well as death. This review endeavors to summarize existing literature on perioperative dysglycemia and provides updates on pharmacotherapy and management of perioperative hyperglycemia and hypoglycemia in surgical patients.